'It is always worth the extra effort': Organizational structures and barriers to collaboration with consumers in mental health research: Perspectives of non‐consumer researcher allies. (28th June 2020) - Happell, Brenda; Gordon, Sarah; Roper, Cath; Scholz, Brett; Ellis, Pete; Waks, Shifra; Warner, Terri; Platania‐Phung, Chris
Abstract: Consumer collaboration in mental health research has demonstrated significant benefits and reflects both contemporary research practice and policy goals for the expected genuine involvement of consumers in all aspects of mental health service delivery. Notable barriers have been identified as impeding consumer researcher positions that must be better understood and ultimately addressed. The aim of this research was to better understand these barriers from the perspectives of non‐consumer researchers who have worked collegially with consumer researchers. We developed a self‐report survey, Consumers as Researchers in Mental Health (CaRiMH) and administered it to non‐consumer mental health researchers in Australia and New Zealand. Findings suggest a lack of organizational structures to support both consumer research and capacity building of consumer researchers. Most consumer researchers were employed casually with no set hours. Although consumer researchers were typically remunerated, inadequate funding and inflexibility of employment were highlighted as major barriers. There was variation in opinion about token involvement of consumer researchers and some uncertainty about whether these roles, where they existed, were actively resisted. Despite the acknowledged barriers, participants were positive about collaborations with consumer researchers. Overall, findings suggest consumer research is unlikely to proliferate without greater attention to organizational structures. A systematic and strategic approach to advancing mental health consumer research is required, including extra‐organizational policy factors.